2011
DOI: 10.1002/j.2161-1882.2011.tb00268.x
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Orientation Minorities in College Counseling: Prevalence, Distress, and Symptom Profiles

Abstract: Sexual minority group members are at a higher risk for mental health difficulties than are heterosexual individuals. The results of this study showed that college student sexual minorities were common in counseling centers and that they were more likely than heterosexual students to seek counseling. The results also showed that sexual orientation groups differed in meaningful ways from one another, and many sexual orientation groups reported higher levels of psychological symptoms than did heterosexual student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
35
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 33 publications
4
35
1
Order By: Relevance
“…The transition to college is characterized by personal exploration, increased responsibilities, and changes in personal and social functioning (Sher et al, 1996;Towbes & Cohen, 1996). It is important to consider the effect of this transition on LGB students, in particular, due to their increased risk of mental health symptomatology across the life span (Cochran & Mays, 2000;King et al, 2008;McAleavey et al, 2011). This study demonstrates that for both LGB and heterosexual students there is a significant increase in psychological distress, coupled with a significant decrease in psychological well-being and cognitiveaffective strengths, over the first semester of university.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The transition to college is characterized by personal exploration, increased responsibilities, and changes in personal and social functioning (Sher et al, 1996;Towbes & Cohen, 1996). It is important to consider the effect of this transition on LGB students, in particular, due to their increased risk of mental health symptomatology across the life span (Cochran & Mays, 2000;King et al, 2008;McAleavey et al, 2011). This study demonstrates that for both LGB and heterosexual students there is a significant increase in psychological distress, coupled with a significant decrease in psychological well-being and cognitiveaffective strengths, over the first semester of university.…”
Section: Discussionmentioning
confidence: 99%
“…Second, although research has suggested that the transition to college may be difficult for youth in general (Towbes & Cohen, 1996), it has not directly considered how the college transition may affect LGB students as compared to their heterosexual peers. Third, much research on sexual minorities has focused on special LGB populations, such as those seeking counseling (McAleavey et al, 2011) or LGB adults of color (Meyer, 2010). Although this research is important, our study advances knowledge of LGB students by including a general college student population making an important developmental transition.…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…If family support of a sexual minority student is not possible, it may be important to help the student identify other sources of enduring social support, such as organizations for gay, lesbian, bisexual, transgender, and queer (GLBTQ) individuals or organizations that are GLBTQ friendly. McAleavey et al (2011) also found that lesbians had lower levels of eating concerns than did heterosexuals. This finding also was echoed by Nelson, Locke, and Castonguay (2011;this issue), whose findings are discussed in more detail later in this article.…”
mentioning
confidence: 90%